SYNTHESIS AND PHARMACOLOGICAL EVALUATION OF 6-CARBETHOXY-5-(3'-BROMOPHENYL)-3-ARYL-2-CYCLOHEXENONES AND 6-ARYL-4-(3'-BROMOPHENYL)-3-OXO-2,3A,4,5-TETRAHYDRO-2H-INDAZOLES (Journal of Sciences, Islamic Republic of Iran)
6-Carbethoxy-5-(3'-bromophenyl)-3-aryl-2-cyclohexenones 2a-j were obtained from the1-Aryl-3-(3'-bromophenyl)-2-propene-1-ones 1a-j by Micheal addition of ethyl acetoacetate, followed by internal Claisen condensation. Reaction of 2a-j with hydrazine hydrate afforded the corresponding 6-Aryl-4-(3'-bromophenyl)-3-oxo-2,3a,4,5-tetrahydro-2H-indazoles 3a-j. The structures of newly synthesized compounds were established on the basis of elemental analyses, IR, NMR and Mass spectral data. The pharmacological evaluations were performed for their anticancer, antitubercular and antimicrobial activities.